2019
DOI: 10.3747/pdi.2018.00175
|View full text |Cite
|
Sign up to set email alerts
|

Burden and Correlates of Hospital Readmissions among U.S. Peritoneal Dialysis Patients

Abstract: Background Hospital readmissions are common among in- center hemodialysis patients, but little is known about read-missions among peritoneal dialysis (PD) patients. Using national administrative data, we aimed to examine the burden and correlates of hospital readmissions among U.S. PD patients. Methods Among 10,505 adult U.S. PD patients with an index admission (first admission after 120 days on dialysis) between 31 January 2011 and 30 November 2014, readmissions were defined as new hospital admissions within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Risk factors for readmission included older age, female sex, diagnosis of liver disease, depression or peripheral vascular disease, and longer length of stay (.5 days) during index admission. Another report of 10,505 patients on PD with index admission during 2011-2014 showed a higher rate of readmission at 29% compared with prior studies (44). The authors identified diagnoses of congestive heart failure and peripheral vascular disease to be independent risk factors, along with hospital stay $4 days.…”
Section: Factors Associated With Readmissionmentioning
confidence: 90%
“…Risk factors for readmission included older age, female sex, diagnosis of liver disease, depression or peripheral vascular disease, and longer length of stay (.5 days) during index admission. Another report of 10,505 patients on PD with index admission during 2011-2014 showed a higher rate of readmission at 29% compared with prior studies (44). The authors identified diagnoses of congestive heart failure and peripheral vascular disease to be independent risk factors, along with hospital stay $4 days.…”
Section: Factors Associated With Readmissionmentioning
confidence: 90%
“…However, the NRD only contains data from community hospitals, and information on patients whose initial admission occurred in other states is not captured by this database; therefore, the rate of hospital readmission in HD patients may be underestimated. Data from the USRDS suggests that IHD, cerebrovascular disease, and HF are associated with hospital readmission in PD patients (12). A recent study indicated that CVDs, including arteriosclerotic heart disease, congestive HF, and transient ischemic attack, could predict 30-day hospital readmission among patients receiving dialysis (14).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that CVDs, including arteriosclerotic heart disease, congestive HF, and transient ischemic attack, could predict 30-day hospital readmission among patients receiving dialysis (14). These studies tended to focus on readmissions among patients receiving a single type (HD or PD) of continuous renal replacement therapy (12,14). In their study, Wetmore et al investigated hospital readmission, focusing on patients frequently hospitalized for CVD (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations